Development and implementation of a web-based radiation dose monitoring information system: A case study of work dose - Arifin, Zaenal; Sutanto, Heri; Widodo, Aris Puji (Edelweiss Applied Science and Technology, 2026)
Radiation worker safety heavily relies on effective and accurate radiation dose monitoring. This study analyzes the Workdose.id Information System, a Radiation Worker Dose Monitoring System, and conducts testing on its reliability, functionality, and system performance. The research methodology includes black-box testing for core system functions, load simulation to evaluate reliability, and response time measurement to assess performance. The results indicate that Workdose.id provides comprehensive functionalities for recording and evaluating worker radiation doses in compliance with regulations. The system demonstrates that no failures were encountered under normal usage scenarios. Average page load times remain within acceptable limits, although latency increases slightly under high user loads. Workdose.id serves as a crucial decision-support system for radiation protection, offering an efficient and reliable digital platform for dose monitoring. However, improvements in system performance and user experience are necessary. These findings contribute to the future development of Workdose.id to enhance radiation worker safety and compliance with regulatory requirements.